2011
DOI: 10.1242/dev.065789
|View full text |Cite
|
Sign up to set email alerts
|

Cell dynamics in fetal intestinal epithelium: implications for intestinal growth and morphogenesis

Abstract: SUMMARYThe cellular mechanisms that drive growth and remodeling of the early intestinal epithelium are poorly understood. Current dogma suggests that the murine fetal intestinal epithelium is stratified, that villi are formed by an epithelial remodeling process involving the de novo formation of apical surface at secondary lumina, and that radial intercalation of the stratified cells constitutes a major intestinal lengthening mechanism. Here, we investigate cell polarity, cell cycle dynamics and cell shape in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 47 publications
1
109
0
Order By: Relevance
“…Recent data indicate that secondary lumina do not form in embryonic gut epithelium. Rather, the new model suggests that an embryonic pseudostratified epithelium experiences interkinetic nuclear migration, apico-basal elongation, cell shape changes, and expansion of the apical surface resulting in villus formation (40). Therefore, it is possible that the fused villi observed in Ezr Ϫ/Ϫ and also Crb3 Ϫ/Ϫ embryos were caused by randomized cell division due to altered spindle orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data indicate that secondary lumina do not form in embryonic gut epithelium. Rather, the new model suggests that an embryonic pseudostratified epithelium experiences interkinetic nuclear migration, apico-basal elongation, cell shape changes, and expansion of the apical surface resulting in villus formation (40). Therefore, it is possible that the fused villi observed in Ezr Ϫ/Ϫ and also Crb3 Ϫ/Ϫ embryos were caused by randomized cell division due to altered spindle orientation.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the role of Crb3 in intestinal development, where dramatic cellular rearrangements lead to villus morphogenesis (39,40), we isolated duodenum from embryonic mice. Crb3 staining verifies the absence of Crb3 in knockout intestine (Fig.…”
Section: Crumbs3mentioning
confidence: 99%
“…Although most knowledge about INM has been derived from studies of the central nervous system (ectodermal origin), it has been demonstrated that INM also occurs during the development of endodermal digestive organs, such as the epithelia emanating from the liver bud [53] or the intestinal epithelia [54]. investigated the development of fetal murine intestine, which is derived from the primitive gut tube, at cellular resolution, and they provided evidence that the epithelium is pseudostratified.…”
Section: Digestive Organsmentioning
confidence: 99%
“…Interestingly, the authors report that growth in epithelial girth is driven by microtubule-and actomyosin-dependent apicobasal elongation, although INM is not greatly disturbed by treatment with microtubule or actomyosin inhibitors in the organ culture. They further showed that knocking out Shroom3, a PDZ-binding domain containing protein on the apical surface, induces apical surface disorganization and the temporal stratification of the epithelium but does not significantly affect INM [54]. These researchers also disrupted Rho kinase function by using its inhibitor and an RNAi construct and showed that cortical contractility by myosin II is required for nuclear translocation.…”
Section: Digestive Organsmentioning
confidence: 99%
“…1A, D and Table 2). During this process, the gut tube expands in length and girth by a combination of proliferation and dynamic acquisition of epithelial polarity [48,49]. Controlled proliferation of cells within the sub-mucosa and muscle layer carefully balance the expansion of the epithelial compartment.…”
Section: E95-e145 Gut Tube Growth and Elongationmentioning
confidence: 99%